A High Level of Circulating Valine Is a Biomarker for Type 2 Diabetes and Associated with the Hypoglycemic Effect of Sitagliptin - Liao, Xiaoyu; Liu, Bingyao; Qu, Hua; Zhang, LinLin; Lu, Yongling; Xu, Yong; Lyu, Zhaohui; Zheng, Hongting (Mediators of Inflammation, 2019)
Background. High levels of branched-chain amino acids (BCAAs) and aromatic amino acids (AAAs) were associated with an increased risk of hyperglycemia and the onset of diabetes. This study is aimed at assessing circulating valine concentrations in subjects with type 2 diabetes (T2D) and in T2D patients and high-fat diet- (HFD-) fed mice treated with the hypoglycemic agent sitagliptin (Sit) and analyzing the association of valine concentrations with metabolic parameters. Methods. Metabolomics in HFD-fed mice were analyzed by gas chromatography-mass spectrometry (GC-MS) systems. Plasma valine concentrations were detected with a commercial kit in 53 subjects with normal glucose levels (n=19), newly diagnosed T2D (n=20), placebo-treated T2D (n=7), or Sit-treated T2D (n=7). Biochemical parameters were also assessed in all participants. Results. Sit treatment markedly changed the pattern of amino acid in HFD-fed mice, especially by reducing the level of the BCAA valine. Compared with the healthy controls, the plasma valine concentrations were significantly higher in the T2D patients (p<0.05). Correlation analysis showed that the plasma valine concentration was positively correlated with the level of fasting plasma glucose (p<0.05). Moreover, the plasma valine concentrations were notably reduced after Sit treatment in T2D patients (p<0.05). Conclusions. Our findings demonstrate an important effect of Sit on the BCAA valine in T2D patients and HFD-fed mice, revealing a new hypoglycemic mechanism of it. Furthermore, the results suggest that the circulating valine level might be a novel biomarker for T2D and restoring the level of valine might be a potential strategy for diabetes therapy.